Conservative treatment of main thoracic adolescent idiopathic scoliosis: Full-time or nighttime bracing? - Ohrt-Nissen S; Lastikka M; Andersen TB; Helenius I; Gehrchen M (SAGE PUBLICATIONS LTD, 2022)
Purpose: To compare treatment efficacy between the Boston full-time brace and the Providence part-time brace in main thoracic adolescent idiopathic scoliosis (AIS). Methods: Patients were treated with either the Boston brace (n = 37) or the Providence brace (n = 40). Inclusion criteria were Risser grade <= 2, major curve between 25 degrees and 40 degrees with the apex of the curve between T7 and T11 vertebrae. Two-year follow-up was available in all patients unless brace treatment had reached endpoint. The primary outcome measure was main curve progression to >= 45 degrees. Results: Median age was 12.6 years and median treatment length at follow-up was 25 months (interquartile range (IQR): 18-32)) with no difference between the groups (p >= 0.116). Initial median main Cobb angle was 29 degrees (IQR: 27-33) and 36 degrees (IQR: 33-38) in the Boston and Providence groups, respectively (p < 0.001). At follow-up, 13 patients (35%) had progressed to >= 45 degrees in the Boston group versus 16 patients (40%) in the Providence group (p = 0.838). Twenty-three patients (62%) had progressed by more than 5 degrees in the Boston group versus 22 patients (55%) in the Providence group (p = 0.685). The secondary thoracolumbar/lumbar curve progressed by more than 5 degrees in 14 (38%) and 18 (45%) in the Boston and Providence groups, respectively (p = 0.548). Conclusions: Despite a larger initial curve size in the Providence group, progression of more than 5 degrees or to surgical indication area was similar in the Boston group. Our results indicate that nighttime bracing is a viable alternative to full-time bracing also in main thoracic AIS.